Review Studi Literatur Sistem Elektrokultur dalam Mempercepat Pertumbuhan dan Perkembangan Tanaman - Aisha Noviadianty; Ardi Mustakim (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
This research aims to analyze the creativity profile and conceptual understanding of students in the sub-concept of animal and plant cell organelles in class XI SMA Negeri 3 Cilegon. The method used is descriptive with a population of 24 students. The sampling technique used was simple random sampling. The instruments used include creativity assessment sheets, creative product assessments, and multiple choice questions. The results show that student creativity in processes and products is in the good category with average scores of 78.69 and 80.7 respectively. Students' understanding of concepts is also relatively good with an average score of 74.8. These findings show that students can understand learning material well through a creative approach.